1976
DOI: 10.4039/ent1081037-10
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Codling Moth (Lepidoptera: Olethreutidae) by Sex Pheromone Trapping of Males

Abstract: Can. Ent. 108: 1021-1030(1976) In Hylemya brassicae (Boucht) little oviposition occurred when access to host plant material was denied. The mustard oil, allyl isothiocyanate (AITC), stimulated the flies into greater activity and attracted them to its source. Sinigrin and four other glucosinolates (mustard oil glucosides) tested induced oviposition. AITC by itself did not induce, oviposition, but in the presence of a glucosinolate, small concentrations of AITC caused an increase in the number of eggs laid. Gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

1979
1979
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…In the latter case mass trapping (Proverbs et al, 1975) and particularly mating disruption strategies (reviewed by Cardé & Minks, 1995) have been tried. Although mass trapping can significantly reduce damage levels, MacLellan (1976) concluded that it was not a feasible control method for C. pomonella, because the low damage thresholds (no more than 1-2% of the crop) required in commercial apple growing could not be achieved. Although the use of the mating disruption technique has become more widespread as a means of controlling the codling moth in commercial apple growing (Waldner, 1994), the method still has considerable drawbacks (see Minks, 1997 for a recent review).…”
Section: Introductionmentioning
confidence: 99%
“…In the latter case mass trapping (Proverbs et al, 1975) and particularly mating disruption strategies (reviewed by Cardé & Minks, 1995) have been tried. Although mass trapping can significantly reduce damage levels, MacLellan (1976) concluded that it was not a feasible control method for C. pomonella, because the low damage thresholds (no more than 1-2% of the crop) required in commercial apple growing could not be achieved. Although the use of the mating disruption technique has become more widespread as a means of controlling the codling moth in commercial apple growing (Waldner, 1994), the method still has considerable drawbacks (see Minks, 1997 for a recent review).…”
Section: Introductionmentioning
confidence: 99%
“…environmenta P factors. Some of the important factors that influence the traps (ALINIAZEE 1976;MCNALLY and BARNES 1981). Knowin the ef P ect of these 2 Materials and methods Tests were carried out in a moderately infested untreated apple orchard located in Madain district, Southern Baghdad province, Iraq.…”
Section: Introductionmentioning
confidence: 99%
“…1976; Willson and Trammel 1980). MacLellan (1976) however, concluded that it was not a feasible method for C. pomonella control due to the low damage thresholds (1–2%) required in commercial apple orchards. Mating disruption has been used to replace persistent chemicals in several parts of the world (Charmillot et al.…”
Section: Introductionmentioning
confidence: 99%
“…Intensive field studies have shown that mass-trapping can significantly reduce codling moth damage (Proverbs et al 1975;Madsen et al 1976;Willson and Trammel 1980). MacLellan (1976) however, concluded that it was not a feasible method for C. pomonella control due to the low damage thresholds (1-2%) required in commercial apple orchards. Mating disruption has been used to replace persistent chemicals in several parts of the world Thomson 1997;Witzgall et al 2008).…”
Section: Introductionmentioning
confidence: 99%